The chiefdom of San Juan Bautista de Végueta. 16th-17th centuries - Adanaqué Velásquez, Raúl (2023)
The study of the colonial cacicazgos is very important because it helps us to understand the strategies carriedout by the curacas or caciques in order to maintain their privileges. The cacicazgo was an institution thatfunctioned in colonial times as an imitation of the one that functioned in Tahuantinsuyo with the Incas, withthe aim of controlling the aboriginal population. The Spanish conquerors took advantage in their own way,conditioning the operation for their benefit. In the old zone of Chimú influence, it was where the first populationtransfers were practiced according to the interests of the encomenderos until the lawyer Lope García deCastro (1564-1569). It was from 1570, with the government of Viceroy Francisco de Toledo (1569-1581),that the foundation of Indian towns with the so-called reductions began to be implemented throughout theviceroyalty. As of those years, the general transfer of the populations to the territories that had previously beenchosen, either on vacant land or owned by curacas, began again. The transfer of the population to the chosenlocation was with the objective of being able to count on the indigenous workforce with greater security andthus they could not evade, since these places were walled or fenced with adobes or sticks.